Results of studies on red snow crab С hionoecetes japonicus in the bathyal zone of the central Japan Sea - Andrey N. Dyominov (Известия ТИНРО)
Deep-water red snow crab is researched in poorly or never surveyed areas of its habitat in the central part of the Japan Sea, as Kita-Yamato Bank and Peter the Great Seamount on the data obtained aboard RV Vladimir Safonov in April-May 2012. The densest aggregations of red snow crab males and females are found at depth 800-1040 m. Total biomass of commercial males of this species is estimated as 7,400 t, including 14 t in the 1.5 km2 area of the top of Peter the Great Seamount where the red snow crab is observed in the first time. The crabs of this mountain are distinguished by small size: on average males - 83.0 mm, females - 58.6 mm (comparing with 99.9 mm males and 65.0 mm females on Kita-Yamato Bank). The results for Kita-Yamato Bank are compared with previous researches of fishing vessels Seisho-maru 68 (September-October 1992), Viera (May-June 2005) and Arctic Orion (April-May 2007) and decreasing of the red show crab stock is detected, in 1/3 for two decades.